The Efficacy of Once-Daily Dose of Phenobarbital in Children with Generalized Tonic-Clonic Epilepsy - Amril A. Burhany; Sofyan Ismael; Hardiono Pusponegoro (Indonesian Pediatric Society, 1995)
In spite of its long half life, phenobarbital is still given twice-daily in the treatment of generalized tonic-clonic epilepsy. This study aims to determine if daily dose of phenobarbital given once differs to that given twice daily. Subjects of this unblinded controlled clinical trial were generalized tonic-clonic epilepsy patients ranging in age from 1-15 years. There were 40 study cases and 42 controls. We gave phenobarbital 4-6 mg/kg/day once-daily for study group and twice-daily dose for control group. History, physical and EEG examination and phenobarbital plasma measurements were obtained a t the beginning of the study and four weeks later. The ratio of the second to first phenobarbital plasma concentrations in the study group was 0.99 while in the control group it was 1.02. The proportion of seizure-free patients in the study group increased from 70% at the beginning to 85% at the end of study, and in the control group from 64.3% to 83.3%. Hyperactivity and irritability increased in both groups, and there were no significant differences in mean serum levels, seizures control, hyperactivity and irritability in both groups. Drowsiness was found in 50% of cases, but statistically significant decrease were found in study group. The compliance of the study group (92.5%) was significantly better than that of the control group (71.4%).